The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1162/jocn_a_00397
|View full text |Cite
|
Sign up to set email alerts
|

Retinotopic and Lateralized Processing of Spatial Frequencies in Human Visual Cortex during Scene Categorization

Abstract: Using large natural scenes filtered in spatial frequencies, we aimed to demonstrate that spatial frequency processing could not only be retinotopically mapped but could also be lateralized in both hemispheres. For this purpose, participants performed a categorization task using large black and white photographs of natural scenes (indoors vs. outdoors, with a visual angle of 24° × 18°) filtered in low spatial frequencies (LSF), high spatial frequencies (HSF), and nonfiltered scenes, in block-designed fMRI recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 91 publications
6
59
0
Order By: Relevance
“…It is important to note that since the DCM analysis was performed on regions of the right hemisphere, as did Kveraga et al (2007), the inferred effective connectivity in our study may primarily apply to the right hemisphere. Besides, to our knowledge, there is no evidence of a symmetric connectivity network between the right and the left hemisphere and previous studies have shown right hemisphere predominance for coarse-to-fine analysis (Musel et al, 2013;Peyrin, Baciu, Segebarth, & Marendaz, 2004;Peyrin, Chauvin, Chokron, & Marendaz, 2003;Peyrin et al, 2005).…”
Section: Endogenous Parametersmentioning
confidence: 57%
See 1 more Smart Citation
“…It is important to note that since the DCM analysis was performed on regions of the right hemisphere, as did Kveraga et al (2007), the inferred effective connectivity in our study may primarily apply to the right hemisphere. Besides, to our knowledge, there is no evidence of a symmetric connectivity network between the right and the left hemisphere and previous studies have shown right hemisphere predominance for coarse-to-fine analysis (Musel et al, 2013;Peyrin, Baciu, Segebarth, & Marendaz, 2004;Peyrin, Chauvin, Chokron, & Marendaz, 2003;Peyrin et al, 2005).…”
Section: Endogenous Parametersmentioning
confidence: 57%
“…Our fMRI results revealed that coarse-to-fine sequences (compared to fine-to-coarse sequences) elicited stronger bilateral activation in three cortical hubs: the occipital cortex (C), the inferior frontal gyrus (IFG), and the fusiform and parahippocampal gyri (FG). The involvement of the occipital cortex in visual perception and in spatial frequency processing has already been well-established using sinusoidal gratings (Henriksson, Nurminen, & Vanni, 2008;Sasaki et al, 2001) and scenes (Musel et al, 2013). Activation in the left inferior frontal gyrus (peak coordinates x, y, z: À36, 16, À10) almost overlaps with the orbitofrontal activation reported by Bar et al (2006;x, y, z: À36, 23, À14) and Kveraga et al (2007;x, y, z: À30, 28, À11).…”
Section: Connectionmentioning
confidence: 83%
“…Cerebral asymmetries have been observed in behavioral studies conducted on healthy participants (Sergent, 1982, 1983; Sergent and Hellige, 1986; Kitterle et al, 1990, 1992; Chokron et al, 2003; Peyrin et al, 2003), in neurological patients (Robertson et al, 1988; Lamb et al, 1990; Robertson and Lamb, 1991; Peyrin et al, 2006; Dos Santos et al, 2013), and from functional neuroimaging studies (Fink et al, 1996, 2000; Martinez et al, 1997, 2001; Heinze et al, 1998; Kenemans et al, 2000; Mangun et al, 2000; Yamaguchi et al, 2000; Wilkinson et al, 2001; Han et al, 2002; Iidaka et al, 2004; Lux et al, 2004; Peyrin et al, 2004; Weissman and Woldorff, 2005; Musel et al, 2013). However, the hemispheric specialization for spatial frequency processing was largely inferred from studies assessing cerebral asymmetries during the processing of global and local information.…”
Section: Neural Correlates Of Spatial Frequency Processing During Scementioning
confidence: 99%
“…Images from the second set are “flipped” by 180° in the midsagital plane, thus providing “mirror” images of the first set. Contrasts between “unflipped” and “left-right flipped” functional volumes from the same experimental condition allow to compare activity in one hemisphere with activity in homologous regions of the other hemisphere (Iidaka et al, 2004; Peyrin et al, 2004, 2005; Musel et al, 2013; see also Cousin et al, 2006 for an application of this method on language processes; Figure 3 ). This method revealed greater activation in the right than the left middle occipital gyrus for LSF scene recognition, and greater activation in the left than the right middle occipital gyrus for HSF scene recognition ( Figure 2B ).…”
Section: Neural Correlates Of Spatial Frequency Processing During Scementioning
confidence: 99%
See 1 more Smart Citation